Analysis of recurrence of risk factors after transcatheter bronchial artery embolization for hemoptysis - Yanchao Dong; Jianli An (Annals of Saudi Medicine)
BACKGROUND: As a proven and preferred technique for hemoptysis, bronchial artery embolization (BAE) cannot avoid the possibility of postoperative recurrence; however, few studies have examined the causes of hemoptysis recurrence after BAE. OBJECTIVES: Identify the risk factors for hemoptysis recurrence after BAE treatment. DESIGN: Retrospective SETTING: Tertiary training and research hospital PATIENTS AND METHODS: A retrospective analysis was conducted on 406 patients with hemoptysis, 55 patients who developed with recurrent postembolization hemoptysis, covering the period from January 2011 to January 2021. Single factor analysis and multiple factor logistic regression were used to analyze high-risk factors for hemoptysis recurrence. MAIN OUTCOME MEASURES: The incidence and risk factors for recurrence hemoptysis associated with transcatheter BAE. SAMPLE SIZE: 406 patients RESULTS: Multivariate logistic regression analysis showed that preoperative computed tomography angiography (CTA) (odds ratio [OR]: 0.052, 95% CI: 0.012–0.225), tumor-related hemoptysis (OR: 20.753, 95% CI: 6.778–63.545), pleural thickening (OR: 3.168, 95% CI: 1.081–9.286), and bilateral lung lesions (OR: 8.442, 95% CI: 2.449–29.101) had a statistically significant impact on the recurrence of hemoptysis after BAE. CONCLUSIONS: Preoperative CTA serves as a protective factor against hemoptysis recurrence, whereas tumor-related hemoptysis, pleural thickening, and bilateral lung diseases are significant risk factors for hemoptysis recurrence following interventional therapy. LIMITATIONS: This was a retrospective analysis of a single center with a small sample, which may have a certain degree of recall bias when collecting data, thus, reducing the reliability of the results.